Integrasi Artificial Intelligence Canva and Crello Sebagai Pengetahuan Digital Pendidikan - Nadilla Aleyda Maqhfira Agustin; Wahyu Insani; Dewimah Putri Tazkiyah; Miftah Farid; Zainal Arifin Ahmad (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
This study aims to provide an in-depth description of the integration of Artificial Intelligence (AI) o the Canva and Crello platforms as digital educational knowledge at SMA Plus Al-Azhar Jember to optimize students' 21st-century skills through interactive visual content aligned with holistic Islamic values. Qualitative methods were applied through in-depth interviews with the principal, teachers, and students, observation of learning sessions, and collection of secondary data such as institutional policies, with data analysis including condensation, presentation, and conclusion formation. The results of the study show positive adaptation dynamics since 2023/2024, including increased student creativity via Canva's Magic Studio feature, collaborative interactions that increase participation, teacher efficiency in material preparation, long-term contributions to digital literacy, as well as challenges such as technology dependency and ethical issues of content authenticity. stated that AI integration is a catalyst for inclusive education transformation. However, challenges such as technology dependency, internet limitations, and the risk of plagiarism are addressed with digital literacy and ethics training.